A pathway to ultracold bosonic 23Na39K ground state molecules. (17th December 2019) - Voges, Kai K; Gersema, Philipp; Hartmann, Torsten; Schulze, Torben A; Zenesini, Alessandro; Ospelkaus, Silke
Abstract: We spectroscopically investigate a pathway for the conversion of 23 Na 39 K Feshbach molecules into rovibronic ground state molecules via stimulated Raman adiabatic passage. Using photoassociation spectroscopy from the diatomic scattering threshold in the a 3 Σ + potential, we locate the resonantly mixed electronically excited intermediate states ∣ B 1 Π, v = 8 ⟩ and ∣ c 3 Σ +, v = 30 ⟩ which, due to their singlet–triplet admixture, serve as an ideal bridge between predominantly a 3 Σ + Feshbach molecules and pure X 1 Σ + ground state molecules. We investigate their hyperfine structure and present a simple model to determine the singlet–triplet coupling of these states. Using Autler–Townes spectroscopy, we locate the rovibronic ground state of the 23 Na 39 K molecule ( ∣ X 1 Σ +, v = 0, N = 0 ⟩ ) and the second rotationally excited state N  = 2 to unambiguously identify the ground state. We also extract the effective transition dipole moment from the excited to the ground state. Our investigations result in a fully characterized scheme for the creation of ultracold bosonic 23 Na 39 K ground state molecules.